Clinical research diagnostic criteria for bipolar illness (CRDC-BP): rationale and validity. - Ghaemi, S. Nassir.; Angst, Jules.; Vohringer, Paul A.; Youngstrom, Eric A.; Phelps, James.; Mitchell, Philip B.; McIntyre, Roger S.; Bauer, Michael.; Vieta, Eduard.; Gershon, Samuel. (Tufts University. Tisch Library., 2022)
Keywords: DSM, RDC, CRDC, Diagnosis, Nosology, Bipolar disorder, Classification.; Springer Open.